Research and Development Expenditures of Innovative Enterprises in the Time of Crisis - Lech, Aleksandra (Comparative Economic Research. Central and Eastern Europe, 2012)
The paper presents the reaction of companies that have been making the largest outlays on R&D in a global scale to the current economic crisis. The analysis paid special attention to what extent R&D investments had been affected in comparison with net sales and profits and how R&D investment were affected across industries and regions. The analysed enterprises reduced their net sales and profits to a greater extent than outlays on research and development, which confirms an anticyclical character of R&D activity in leading innovative enterprises. It has to be noted that in an analysed sample some companies significantly decreased outlays on R&D, however, there were some that increased these outlays in spite of worsening economic performance. Among investigated sectors the one that proved to be the most crisisresistant was the pharmaceuticals & biotechnology sector - classified as high technology, whereas the most crisis-prone one was the automotive sector. Nonetheless, the thesis that high tech industries are more crisis-resistant cannot be substantiated – outlays on research and development in the following sectors: computer production, office equipment, semiconductors, telecommunications equipment (technology hardware & equipment) – classified as high technology in 2009 were reduced in relation to year 2008. In an analysed group of enterprises the smallest "resistance" to crisis was observed in American companies. The enterprises from the EU also reduced research and development expenditures but the pace of a fall in these expenditures was smaller than in the case of American companies.